Suprachoroidal implantation of corticosteroid slow release implants for the treatment of cystoid macular edema - Ben Asani; Franziska Kruse; Jakob Siedlecki; Johannes Benedikt Schiefelbein; Benedikt Schworm; Julian Klaas; Tina Herold; Siegfried G. Priglinger (Scientific Reports)
Abstract In cases of an unstable iris-lens diaphragm, intravitreal corticosteroid slow-release implants (CSRI) may accidentally migrate into the anterior chamber, leading to damage to the corneal endothelium. The purpose of this study was to evaluate the efficacy and safety of a suprachoroidal application of these primarily intravitreal implants to address this issue. In this single-center, retrospective proof of principle study, we observed consecutive cases of patients receiving dexamethasone and fluocinolon acetonide implants that were administered into the suprachoroidal space in patients with CME and instability of the iris-lens diaphragm. Treatment responses of the CME on OCT, incidence of secondary intraocular pressure increases, visual acuity and surgery related complications were evaluated. In total, 16 patients were treated and mean follow up was 1.8 ± 0.97 months. The procedure was well tolerated with no severe intraoperative or postoperative side effects. Mean central retinal thickness (CRT) decreased significantly from 563.13 to 382.12 (p = 0.002). There was no incidence of steroid induced glaucoma. Mean best corrected visual acuity (BCVA) significantly improved from 1.07 logMAR to 0.65 logMAR (p = 0.01). Suprachoroidal implantation of corticosteroid slow-release implants proves to be a safe and feasible alternative for complex eyes with CME and a disruption of the anterior-posterior segment border.